Using Authentic Materials and Vocabulary Profiler to Enhance Vocabulary Learning - Patrisius Djiwandono (KLAUSA (Kajian Linguistik, Pembelajaran Bahasa, dan Sastra), 2018)
The paper reports a research about the effect of authentic materials and the use of vocabulary profiler on some EFL learners’ master of vocabulary. An intact class of 21 students was taught Vocabulary lesson, which amounted to 100 minutes of class session every week. In addition to this regular intentional learning, they were instructed to read authentic materials and utilize a vocabulary profiler to obtain a vocabulary profile of the materials. They were taught how to interpret the result of the profiling. Next, they were asked to show their texts on a blog so as to allow their classmates to learn new words from the texts. Questionnaires were used to elicit their opinions on this teaching technique. At the end of the semester a post-test was administered to determine the gains in their vocabulary mastery. While there was an apparent gain in their command of 5000-level English words, they did not make a similarly encouraging achievement in the new words from the texts. An explanation that accounts for the finding was offered. Meanwhile, the answers from the questionnaires seemed to reflect their positive attitude toward the use of authentic materials in this fashion.